Overview of Waste Management and Fly Density Level in 2021 - Maria Flaviana Tefa; Deviarbi Sakke Tira; Soleman Landi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Disease vectors are organisms that carry pathogenic viruses or bacteria and parasites from infected hosts to other hosts. Vector communicable diseases are influenced by the physical, biologica, and socio-cultural environment. Mosquitoes, fleas, and flies are vectors of infectious disease carriers. These vectors carry infectious diseases such as malaria, filariasis, bubonic plague, typhus, and diarrhea. One of the vectors that cause diarrhea is the fly. The presence of flies can be an indication of poor hygiene. This study aims to determine the description of waste management and the density level of flies in traditional markets in Kupang City. The type of research is a descriptive survey. The samples were the yellow troops and market managers at the Inpres, Kasih, and Oeba Market. The analysis was carried out using the SPSS application. The results of the study indicate that taste management in the Kupang City Traditional Market is not fully effective on average.